2014
DOI: 10.1021/bi401638u
|View full text |Cite
|
Sign up to set email alerts
|

The SNARE Motif of Synaptobrevin Exhibits an Aqueous–Interfacial Partitioning That Is Modulated by Membrane Curvature

Abstract: The structure and interfacial association of the full-length vesicle SNARE, synaptobrevin, were compared in four different lipid environments using nuclear magnetic resonance and electron paramagnetic resonance spectroscopy. In micelles, segments of the SNARE motif are helical and associated with the interface. However, the fraction of helix and interfacial association decreases as synaptobrevin is moved from micelle to bicelle to bilayer environments, indicating that the tendency toward interfacial associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 47 publications
(110 reference statements)
4
33
0
Order By: Relevance
“…The authors concluded that this increase was because of a structural rearrangement of syb2, but not the acceptor t-SNARE complex. We think that cholesterol might also change the partitioning of the N-terminal half of the SNARE motif of syb2 between the surface of the vesicle bilayer and the surrounding solution that we observed to be highly dependent on membrane curvature (70). Based on fluorescence measurements, this partitioning is not expected to happen with the preassembled acceptor t-SNARE complex in the target membrane (71).…”
Section: Discussionmentioning
confidence: 81%
“…The authors concluded that this increase was because of a structural rearrangement of syb2, but not the acceptor t-SNARE complex. We think that cholesterol might also change the partitioning of the N-terminal half of the SNARE motif of syb2 between the surface of the vesicle bilayer and the surrounding solution that we observed to be highly dependent on membrane curvature (70). Based on fluorescence measurements, this partitioning is not expected to happen with the preassembled acceptor t-SNARE complex in the target membrane (71).…”
Section: Discussionmentioning
confidence: 81%
“…The dynamic prefusion structures of the vesicle SNARE synaptobrevin (Ellena et al 2009) and the target membrane SNARE syntaxin (Liang et al 2013) have been solved by solution NMR in lipid micelles. These structures were also more folded than their soluble counterparts in the absence of lipids and therefore suggested lipid-assisted folding (and perhaps fusion) pathways that are further modulated by membrane curvature (Liang et al 2014). Eager spectators may be in for many more revealing surprises before we fully understand the folding-fusion coupling in the intracellular and viral membrane fusion field!…”
mentioning
confidence: 99%
“…Some lipid-binding amphipathic helices also interact with proteins, as demonstrated for the synaptobrevin2 SNARE domain (Ellena et al, 2009;Liang et al, 2014) or the N-terminal mitochondrial presequences that interact with a hydrophobic groove on the Tom20 receptor (reviewed in Chacinska et al, 2009). Unlike Pom33-CTD, which appears to be improperly recognized by this mitochondrial translocation machinery (Fig.…”
Section: Discussionmentioning
confidence: 98%